The Role of the Archives in a Digital World - Peucker, Paul (Journal of Moravian history, 2022)
Digitization has increased the accessibility of archival holdings. At the same time, digitization not only changes the relationship between the archivist and the researcher, but it also changes the way records are described. The author argues that, in order to remain relevant, archives need to different programs and develop into centers of expertise.